Redox active viologen derivatives for aqueous and non-aqueous organic redox flow batteries applications - Cho, Yunho; Kye, Hyojin; Kim, Bong-Gi; Kwon, Ji Eon (한국공업화학회, 2024)
Redox-flow battery (RFB) is considered as one of the most promising candidates for large-scale energy storage systems. Due to the potential problems of inorganic electrolytes, such as low solubility, high toxicity, and corrosiveness, redox-active organic materials (ROMs) have been actively studied to replace the inorganic electrolytes for RFBs. Among the ROMs, viologen derivatives are of great interest for p-type anolytes due to their low redox potential, high solubility, and stable characteristics. This review briefly discusses the recent developments in molecular engineering strategies related to viologen derivatives for aqueous and nonaqueous organic RFBs. In addition, promising applications of viologen-based RFBs, such as solar energy storage and desalination, have been briefly introduced. The structure-related redox properties of the viologen derivatives principally described in this review are expected to pave the way for the development of redox-active materials, enhancing ORFB performance to extend practical applications as green energy storage systems.